Standalone PV solar using LED flood light for street lighting - Amedan, Rubiatul Adawiah (2017)
Maximum power point tracking (MPPT) is a technique to extract maximum energy from the photovoltaic (PV) system. This work presents the designing and simulating the PV modules by using Perturb and Observe algorithm to track maximum power point. To develop PV system with this P&O algorithm, this system is constructed and simulates using MATLAB Simulink software. The hardware process of this project is implemented by using Arduino, for verification of the results. This design includes PV panels, boost converter, charge controller and Led load.